2011
DOI: 10.1007/s11104-011-0761-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sand burial, soil water content and distribution pattern of seeds in sand on seed germination and seedling survival of Eremosparton songoricum (Fabaceae), a rare species inhabiting the moving sand dunes of the Gurbantunggut Desert of China

Abstract: Sand burial, persistent seed bank and soil water content (SWC) are three factors that potentially can affect regeneration in sand dune plant populations. To evaluate the effects of these three factors on population regeneration of Eremosparton songoricum, a rare and endangered legume, we investigated seed germination, seedling emergence and seedling survival in greenhouse and controlled field experiments in different sand dunes microsites. Freshly matured seeds are physically dormant, and the highest germinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 54 publications
4
55
0
1
Order By: Relevance
“…3a). Liu et al (2011) and Zhu et al (2014) also found similar results and thought they were related to greater humidity (soil moisture) around these seeds in the top layer. The lowest seed germination rates at the 5 cm burial depth may be related to low oxygen in the sand (Vleeshouwers 1997) or the exhaustion of seed reserves during germination (Chen andMaun 1999, Liu et al 2011).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…3a). Liu et al (2011) and Zhu et al (2014) also found similar results and thought they were related to greater humidity (soil moisture) around these seeds in the top layer. The lowest seed germination rates at the 5 cm burial depth may be related to low oxygen in the sand (Vleeshouwers 1997) or the exhaustion of seed reserves during germination (Chen andMaun 1999, Liu et al 2011).…”
Section: Discussionmentioning
confidence: 54%
“…Burial depth has been demonstrated to have an effect on seed germination (Zhang and Maun 1994, Chen and Maun 1999, Li et al 2007, Guo et al 2010, Liu et al 2011, Redondo-Gómez et al 2011, Zhu et al 2014. For example, the highest seedling emergence for wildrye occurred at a 1-cm depth (Zhu et al 2014), whereas it was 2-cm for Pitcher's thistle (Chen and Maun 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2), Meanwhile, the harsh environmental conditions in deserts, such as drought, high temperature, and so on, result in high death rates. For example, the survival rate of Eremosparton songoricum (Fabaceae) in the Gurbantunggut Desert is only 2% (Liu et al, 2011). Haloxylon ammodendron is the dominant species in the Gurbantunggut Desert.…”
Section: The Relationship Between the Survival Of Haloxylon Ammodendrmentioning
confidence: 99%
“…VPD indicates that the degree of atmospheric drought also controls the evaporation of surface soil water and the transpiration rate of vegetation. When atmospheric drought is severe, water evaporation loss on the surface soil of longitudinal dunes and water consumption of vegetation transpiration are higher (Liu et al, 2011). Consequently, the death rate of Haloxylon ammodendron seedlings will also be higher (Fig.…”
Section: The Relationship Between the Survival Of Haloxylon Ammodendrmentioning
confidence: 99%